Reading of Nature and Women in the Select Novels of Margaret Atwood: An Ecofeminist Approach - Jitendra Kumar Bharti (The Creative Launcher, 2019)
Ecofeminism is a philosophical and political movement and theory which commingle or puts together demonstrate male domination of society. The term Ecofeminism is coined in the 1970s by the French writer Francoise d' Eaubonne in her book Le Feminisme ou La Mort (1974). The term ecofeminism unites Ecology (a scientific study and analysis of interaction among organisms and their environment) and Feminism (a social and political movement which advocates for women rights) and attempts to eradicate al forms of social injustice. It draws parallel between the both women and nature because both are dominated by men. The movement ecofeminism is the result of gradual development. In the beginning some women activists participated to preserve environment, but in the late 20th century these women activists began to work to protect wild life, food, air and water. We may see, in 1973, in Northern India, rise of a movement led by women activists to protect forests from deforestation that is known as ‘Chipko movement.’